(untitled) (Bangladesh Journal of Botany, 2010)
Peganum harmala L. (Zygophyllaceae) is burned into ash-cake ("Askar") in Emirdag (Afyon), Middle Anatolia. The plant has been widely known as Üzerlik in Anatolia in addition to other names. In this study, both the production and usages of the ash-cake from Peganum harmala L. in Anatolia has been described. It has ethnobotanical importance in protecting silk and hair and as fumigant. Key words: Peganum harmala L.; "Askar" (charcoal); Ethnobotany; Anatolia; Turkey DOI: 10.3329/bjb.v38i2.5152 Bangladesh J. Bot. 38(2): 211-213, 2009 (December)